Autoimmune-related encephalitis during treatment with nivolumab for advanced head and neck cancer: a case report. Issue 6 (December 2020) - Guidi, Alessandro; Violati, Martina; Blasi, Miriam; Ferrari, Elettra; Luciani, Andrea; Codecà, Carla; Ferrari, Daris
Introduction: Head and neck cancer represents a variety of tumors involving different organs in the cervical district, burdened by poor prognosis when diagnosed in an advanced stage. Immunotherapy with both anti-PD-1 nivolumab and pembrolizumab has the aim of increasing overall survival for patients with this malignancy. We report the first case of immune-related encephalitis caused by nivolumab in this setting of disease and present a brief review of the literature. Case description: A 60-year-old woman had been treated with concomitant chemoradiotherapy for a locally advanced human papillomavirus–negative squamous cell carcinoma of the tonsil. After local recurrence, she was treated with platinum-based first-line chemotherapy, followed by nivolumab at further progression within 6 months. Nivolumab was administered for 19 weeks, then discontinued due to the occurrence of immune-related hypothyroidism and grade 2 diarrhea. A month after the onset of the endocrinopathy, the patient also developed steroid-responsive encephalitis, considered as a consequence of anti-PD-1 therapy. One year after discontinuation of immunotherapy, toxicities have resolved and the patient is maintaining a complete radiologic response. Conclusions: Immunotherapy is a relatively new and promising therapy in the field of oncology. Its mechanism of action, which aims to stimulate the immune system against cancer cells, is not comparable to systemic and cytotoxic chemotherapy, which directly attacks and destroys malignant cells. Despite these differences, immunotherapy is not to be considered free from side effects, sometimes life-threatening.